An Analysis on Onomatopoeic Words and their Translation Procedures in Harry Potter and The Prisoner of Azkaban and Its Translation Version - Leni Tiwiyanti (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2017)
Novel as the most famous genre of literature always succeeds to please its readers with its own way. It offers many stylistic language features such as onomatopoeia that can alure the readers to enter its world. Onomatopoeia is one of the most appealing feature in the novel Harry Potter and The Prisoner of Azkaban. This research discusses the onomatopoeic words in Harry Potter and The Prisoner of Azkaban by J.K. Rowling and its translation version Harry Potter dan Tawanan Azkaban. For the purpose of the research, two problems are formulated. The first problem is what word classes of onomatopoeia that are found in the novel Harry Potter and The Prisoner of Azkaban. The second problem of the research is on the procedures applied in translating the onomatopoeia found in the novel. This research is a qualitative and library research. The data are the onomatopoeia words found in the novel Harry Potter and The Prisoner of Azkaban by J.K. Rowling and its translation version Harry Potter dan Tawanan Azkaban.Based on the research analysis, followings are the answers to the research problems respectively. From the data collected, there are 58 onomatopoeic words found. The onomatopoeic words are of different word classes; namely verb, noun, adjective and interjection. Most of the onomatopoeic words are verbs. To answer the second problem, there are five translation procedures used by the translator in translating the onomatopoeic words of the source text into the target text. They are borrowing (2 data), literal translation (14 data), transposition (8 data), modulation (1 data) and equivalence (33 data). Equivalence appears to be the most frequently used.